2021
DOI: 10.3390/ijerph18168731
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Restorative Effects of Campus Environments on College Students in the Context of the COVID-19 Pandemic: A Case Study at Northwest A&F University, Shaanxi, China

Abstract: During the COVID-19 outbreak, college students experienced different periods of isolation on campus, which has had an impact on students’ mental health. Based on ART theory, this study randomly selected students at Northwest A&F University, Shaanxi, China and distributed questionnaires in order to evaluate the psychological recovery effect of campus environment during the epidemic. The results showed that: (1) There were significant differences in the psychological restoration of four types of campus envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 63 publications
1
27
2
Order By: Relevance
“…The campus under construction will generate noise, dust, and visual experiences unrelated to the natural environment ( 75 ). Mounting evidence showed that disorder and confusion are determined by the artificial structures in the environment, which can affect students' landscape preferences and positive emotions ( 4 , 52 ). In addition, the lockdown of universities during the COVID-19 epidemic can also affect students' landscape preferences ( 76 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The campus under construction will generate noise, dust, and visual experiences unrelated to the natural environment ( 75 ). Mounting evidence showed that disorder and confusion are determined by the artificial structures in the environment, which can affect students' landscape preferences and positive emotions ( 4 , 52 ). In addition, the lockdown of universities during the COVID-19 epidemic can also affect students' landscape preferences ( 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the lockdown of universities during the COVID-19 epidemic can also affect students' landscape preferences ( 76 ). UA has now gradually reopened with the effective control of the epidemic, but strict social distancing measures are still in place for students ( 4 ). Our survey was conducted approximately 5 months after the reopening of UA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the travel restrictions set in place during the COVID-19 pandemic, students spend even more time on campus. Therefore, it is necessary and urgent to investigate restorative sites on campus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%